Respostas
respondido por:
1
Boa tarde Josemateus
3^(x+2) - 3^(x + 1) + 3^x + 3^(x - 1) + 3^(x - 3) = 16119
3^x * (9 - 3 + 1 + 1/3 + 1/27) = 16119
3^x * (7 + 1/3 + 1/27) = 16119
3^x * (189 + 9 + 1)/27 = 16119
3^x * (199/27) = 16119
3^x = 16119*27/199 = 2187 = 3^7
x = 7
3^(x+2) - 3^(x + 1) + 3^x + 3^(x - 1) + 3^(x - 3) = 16119
3^x * (9 - 3 + 1 + 1/3 + 1/27) = 16119
3^x * (7 + 1/3 + 1/27) = 16119
3^x * (189 + 9 + 1)/27 = 16119
3^x * (199/27) = 16119
3^x = 16119*27/199 = 2187 = 3^7
x = 7
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás